Budget surplus goal experiments in Australia and Sweden. Issue 5 (3rd September 2017) - Brenton, Scott; Pierre, Jon
ABSTRACT: From the mid-1990s until the 2008 financial crisis, two countries, each with different political, administrative and capitalist traditions, embarked on a radical macroeconomic policy experiment. Australia and Sweden took earlier New Public Management reforms to an ideological extreme, and pursued a profit-like goal for the public sector, in promising and delivering annual budget surpluses. From a historical institutionalist perspective, we challenge existing public choice theories and the guardian-spender framework to show how fears of crisis, party dynamics and ideological reassessments on the centre-left, and the elevation of finance and economics ministers and ministries resulted in an unlikely political and electoral consensus. Furthermore, this occurred without constitutionalised or officially strict rules, as has been the trend in other countries, but was achieved through less formal yet influential 'rules of the game' with stricter interpretations. What is even more perplexing is that Australia and Sweden do not have superior economic records to show for this experiment and experienced the same challenges as other countries during the 2008 financial crisis. Yet, they are still reluctant to definitely abandon the policy.